MUSIK DANGDUT DAN IRONI PENDIDIKAN SENI DI YOGYAKARTA - Mohammad Khatibul Umam (Jurnal Sosiologi Reflektif, 2014)
In the last few years, Indonesia has a lot of arts and cultures that were considered by out of this country as theirs such as Reog Ponorogo also some folk songs had been reasonable and the society infuriated with. Especially for the people that were living in the rural area, as owner of the identity. This condition made the people got warmed up and it was coming almost from all of the circle of society. However they could be learning by that. The people today are getting the picture and open their eyes which they convinced that arts and cultures that they had are a very important asset. In music, Dangdut is a nation’s cultural assets, as identity and should be preserved by us. Unfortunately, it was as if the government does not care about. Mainly they are as policy maker in education. There is no Dangdut in curriculum. whereas it has been learnt by 70 countries in the world. It is slowly disliked by, even abused verbally, and abandoned. They made us to look down on and leaving the identities.